KONSELING ISLAM DENGAN PENDEKATAN COGNITIVE BEHAVIOURAL THERAPY (CBT) UNTUK MENGATASI KENAKALAN REMAJA [ISLAMIC COUNSELING WITH COGNITIVE BEHAVIORAL THERAPY (CBT) APPROACH TO OVERCOME JUVENILE DELINQUENCY] - Eni Kuswatun; N Nurjannah; D Depriansya (Journal of Contemporary Islamic Counselling, 2021)
This study aims to assist AM clients in solving the problems they face causing juvenile delinquency using Islamic counseling with cognitive behavioral therapy (CBT) approach. Islamic counseling using the cognitive behavioural therapy (CBT) approach can be said to have an important role in positive outcomes in counseling. This research method uses the action research method of Islamic guidance and counseling with the cognitive begavioural therapy (CBT) approach. The counseling process of five sessions discusses what happened to the client. The conclusion from the results of this study can show that Islamic counseling with cognitive behavioural therapy (CBT) approach can change the client’s cognitive and behavior, namely positive behavior, good social interaction, and time discipline. So that, the counseling process shows changes in the client’s state of mind and behavior so that behavior negative that appears to be positive behavior.